Influence of hoop restraint on damage evolution, ions diffusion and multi-scale mechanical properties in concrete exposed to external sulfate attack - Jierong Cao; Liping Xu; Gang Xu; Ming Jin; Qingjun Ding; Jiaping Liu; Chuansheng Xiong; Zuquan Jin (Journal of Materials Research and Technology)
This paper presents a systematic study on the influence of the hoop restraint effect of steel tubes on the damage evolution, ions diffusion and multi-scale mechanical properties changes in concrete specimens under the external sulfate attacks (ESA). Visual appearance, ion diffusion, dynamic modulus of elasticity and Vickers hardness were used to characterise the damage evolution, diffusion characteristics and macro/micro-mechanical changes of free/restrained expansion specimens caused by the ESA. Results indicate a lower permeation rate of sulfate ions into the matrix interior and a leaching rate of calcium ions from the matrix in the restrained expansion specimens compared with the free expansion ones. The hoop restraining stresses induced by the hoop restraint suppress the cracking of specimens, leading to a higher dynamic modulus of elasticity and Vickers hardness value in the restrained expansion specimens compared with the free expansion ones, which significantly reduces the deterioration exposed to the ESA. Hopefully, this study may offer the theoretical basis for the design of sustainable and durable concrete under the ESA.